Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1029/2009ja014943
|View full text |Cite
|
Sign up to set email alerts
|

Coseismic ionospheric disturbances triggered by the Chi‐Chi earthquake

Abstract: [1] At 17:47 UT on 20 September 1999, a large earthquake of magnitude M w 7.6 struck the central Taiwan near a small town of Chi-Chi. The ground-based receivers of the global positioning system (GPS) in the Taiwan area detected coseismic ionospheric disturbances (CIDs) in the total electron content (TEC) triggered by the Chi-Chi earthquake. When the CIDs travel away from the origin on the Earth surface and then propagate into the ionosphere, their amplitudes and periods generally become smaller and longer, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 33 publications
1
75
0
Order By: Relevance
“…For those traveling below the mesopause of 90 km altitude, the average AGW speeds are about 300-400 m/s (Liu et al, 2006), while for those departing with relatively high elevation angles and mainly traveling in the ionosphere (or thermosphere) above 100 km altitude, the associated average AGW speeds could be up to 700-1100 m/s (cf. Artru et al, 2004; Heki and Ping, 2005;Liu et al, 2010). Therefore, the speed of 900 m/s suggests the 2 nd STID being related to AGWs mainly traveling in the ionosphere of about 200 km altitude, which is close to the value of 1032-1045 m/s given by Liu et al (2011) and the 1 km/s (1000 m/s) given by Rolland et al (2011).…”
Section: Discussionmentioning
confidence: 72%
“…For those traveling below the mesopause of 90 km altitude, the average AGW speeds are about 300-400 m/s (Liu et al, 2006), while for those departing with relatively high elevation angles and mainly traveling in the ionosphere (or thermosphere) above 100 km altitude, the associated average AGW speeds could be up to 700-1100 m/s (cf. Artru et al, 2004; Heki and Ping, 2005;Liu et al, 2010). Therefore, the speed of 900 m/s suggests the 2 nd STID being related to AGWs mainly traveling in the ionosphere of about 200 km altitude, which is close to the value of 1032-1045 m/s given by Liu et al (2011) and the 1 km/s (1000 m/s) given by Rolland et al (2011).…”
Section: Discussionmentioning
confidence: 72%
“…Liu et al (2006a) observed 2 types of STIDs with traveling speeds of 2.5 km s -1 and 370 m s -1 triggered by the 24 December 2004 M 9.3 Sumatra earthquake. Liu et al (2010) found that the STIDs triggered by the M 7.6 Chi-Chi earthquake range from 700 to 900 m s -1 . Astafyeva et al (2009) analyzed STIDs induced by the 4 October 1994 M 8.1 Kurile earthquake and found that starting from about 600 -700 km away from the epicenter, the disturbance seems to divide into two perturbations which propagate with different velocities, one at about 3 km s -1 and the other at about 600 m s -1…”
Section: Observation and Interpretationmentioning
confidence: 99%
“…Recently, the total electron content (TEC) derived from data recorded by dense ground-based receivers of the global positioning system (GPS) have been employed to examine STIDs such as Rayleigh, gravity, shock, and tsunami waves triggered by earthquakes (Calais and Minster 1995;Afraimovich et al 2001;Ducic et al 2003;Artru et al 2005;Heki and Ping 2005;Astafyeva and Afraimovich 2006;Jung et al 2006;Liu et al 2006b;Astafyeva and Heki 2009;Astafyeva et al 2009;Liu et al 2010Liu et al , 2011. Based on Calais and Minster (1995), most scientists find the timedistance relationship between the triggered disturbances and the epicenter to estimate STID speeds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are detected as abnormal changes in the total electron content obtained from analyses of GPS signals, so-called GPS-TEC (Liu et al, 2010;Rolland et al, 2010;Galvan et al, 2011). The most widely accepted causes of such GPS-TEC anomalies are Rayleigh waves and tsunamis.…”
Section: Above the Ground Surfacementioning
confidence: 99%